Postseismic GRACE and GPS observations indicate a rheology contrast above and below the Sumatra slab. Issue 7 (24th July 2015) - Broerse, Taco; Riva, Riccardo; Simons, Wim; Govers, Rob; Vermeersen, Bert
Abstract More than 7 years of observations of postseismic relaxation after the 2004 Sumatra‐Andaman earthquake provide an improving view on the deformation in the wide vicinity of the 2004 rupture. We include both Gravity Recovery and Climate Experiment (GRACE) gravity field data that show a large postseismic signal over the rupture area and GPS observations in the back arc region. With increasing time GPS and GRACE show contrasting relaxation styles that were not easily discernible on shorter time series. We investigate whether mantle creep can simultaneously explain the far‐field surface displacements and the long‐wavelength gravity changes. We interpret contrasts in the temporal behavior of the GPS‐GRACE observations in terms of lateral variations in rheological properties of the asthenosphere below and above the slab. Based on 1‐D viscoelastic models, our results support an (almost) order of magnitude contrast between oceanic lithosphere viscosity and continental viscosity, which likely means that the low viscosities frequently found from postseismic deformation after subduction earthquakes are valid only for the mantle wedge. Next to mantle creep, we also consider afterslip as an alternative mechanism for postseismic deformation. We investigate how the combination of GRACE and GPS data can better discriminate between different mechanisms of postseismic relaxation: distributed deformation (mantle creep) versus localized deformation (afterslip). We conclude that the GRACE‐observed gravity changes rule out afterslip as the dominant mechanism explaining long‐wavelength deformation even over the first year after the event.